Study on the basic principles of judo instructions in dutch judo leaders - for instructions of children - Takahashi, S.; Nose, S.; Kimura, M.; Nakamura, I.; Koyama, K.; Nukai, M.; Shoshida, K.; Mori, H.; Yogi, Y.; Takahashi, K.; Ishii, T.; Tanaka, H.; et al. (Association for the Scientific Studies on Judo, Kodokan, 2021)
The purpose of this study was to clarify the teaching philosophy of Dutch Judo leaders, focusing on Judo teaching for children. In addition, for the purpose of obtaining more objective evidence, we also requested the provision of instructional videos. The obtained results are as follows, and it became apparent that the Dutch leaders themselves are constantly learning how to teach. It is required that we must reconsider the training system for Japanese Judo Instructor and physical education teachers in future, to understand "Fun Judo lessons" and "Safe Judo instruction" from a global perspective.(1) The results of the responses "Children's motivation 31%" and "Fresh feeling 22%" suggest that Dutch Judo leaders attach great importance to motivation and ingenuity in teaching children.(2) In Japan, the primary issue of Judo instruction has long been regarded as its "safety", but in the Netherlands as well, its "safety 14%" is the guiding principle as shown by the questionnaire results.(3) It was cleared that Dutch Judo leaders also sympathize with "Recharge of children's ability to learn by themselves" and "Interaction between leaders and children" in their guiding principles. It was also suggested that Dutch Judo leaders thought Judo instruction was not limited to the instruction of Judo technology, but it emphasized the learning of the child's mind. It is noteworthy and meaningful.(4) The answer results of "Easy to understand 17%" and "Fresh feeling 22%" indicate that Judo instructors always stand on the side of the learner. At the same time, it is suggested that the subjects of this survey are constantly learning about teaching methods.